Penerapan Modul Ajar Berbasis Kurikulum Merdeka II UPT SD Negeri 323 Gresik - Faridahtul Jannah; Thooriq Irtifa’ Fathuddi (SOKO GURU: Jurnal Ilmu Pendidikan, 2023)
his paper aims to discuss the implementation of independent learning curriculum-based teaching modules. The approach in this study uses a qualitative approach. Analysis of this research data using descriptive analysis. In this analysis, the data is interpreted descriptively and presented in a narrative manner. The results of the teaching module research are implemented at UPT SD Negeri 323 Gresik which is an independent curriculum body which is a substitute for lesson plans. The independent curriculum teaching module is a substitute for lesson plans which are formatted and varied in nature which includes learning material/content, learning methods, interpretation, and evaluation techniques which are arranged in a systematic and riveting manner to achieve the expected indicators of success. The teacher develops teaching modules before carrying out learning in the classroom. One of the functions of the teaching module is to reduce the teacher's burden in presenting content so that the teacher can have a lot of time to become a tutor and help students in the learning process.